Hubungan Jarak Kehamilan dengan Kejadian Stunting di Puskesmas Pargarutan Tapanuli Selatan Tahun 2023 - Gentina Gentina; Erin Padilla Siregar (The Journal General Health and Pharmaceutical Sciences Research, 2023)
Based on the results of Basic Health Research (Riskesdas) in 2013, the prevalence of stunting among toddlers in Indonesia was 37.2%. Then in 2018 there was a national decline to 30.8% (RI Ministry of Health, 2018). Thus, the incidence of stunting in Indonesia is still a problem that needs consideration because the national prevalence is still above the tolerance set by WHO, which is only 20%. The aim is to determine the relationship between pregnancy spacing and the incidence of stunting at the South Tapanuli Pargarutan Community Health Center in 2023. Stunting is caused by several factors, one of which is namely maternal factors (mother's knowledge regarding nutritional status, exclusive breastfeeding and complementary foods for breast milk. The type of research used in this research is quantitative research with a cross sectional research design. The sample for this study was 68 people. Based on the results of statistical tests using the Chi-Square test, it was found that p value is 0.042